MODERN ASPECTS OF NONPARASITIC LIVER CYSTS - I.A. KOPYTIN; V.V. IVANOV; V.B. FILIMONOV; G.Y. ZHURAVLYOV; V.S. FOMIN; I.V. ABRAMOV (Avicenna Tajik State Medical University, 2023)
Objective: The relevance of nonparasitic cysts of the liver (NPCL) is related to their steadily increasing incidence, high recurrence rates, delayed diagnosis, and potential complications. In general, hepatic cysts (HCs) are classified into several types, including simple and complex, false and true. Simple cysts are mainly congenital but also occur in polycystic liver disease. Complex cysts include mucinous neoplasms, echinococcal cysts, hemorrhagic cysts, cystic hepatocellular carcinoma, and other rare lesions. Nonparasitic cystic liver lesions do not usually cause symptoms, and their characteristics are not specific. In 15% of cases, nonspecific signs (flatulence, nausea, dyspepsia) accompany pain. Diagnosis of NPCL is based on data from ultrasound, CT, or MRI of the abdominal organs. There still needs to be a consensus on surgical treatment indications or the effectiveness and feasibility of its various methods. Many surgical interventions for NPCL treatment include puncture drainage, multiple minimally invasive (laparoscopic) surgery options, and open methods. In clinical practice, laparoscopic fenestration, associated with fewer complications and faster recovery, has become widespread. However, significant progress has yet to be achieved in reducing NPCL recurrence rates despite advances in surgical treatment. Therefore, multiple studies are underway to improve treatment options for this medical condition.